DEVELOPMENT OF ELECTRONIC LEARNING PLATFORM “PHONETIC LABELING FEATURES” (OLAF) MICROSOFT EXCEL 2013 BASED - Prasodjo, Pandu; Darmawan, Ach. Anang; Isgandi, Yiyin (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Phoneme labeling is a method to define a phoneme features. Phoneme is the smallest meaningful unit of sound which classified by voiced/voiceless, place of articulation, and manner of articulation. To label a phoneme based on its classification correctly, students of English Education department who programmed Introduction to Linguistics got difficulty. Therefore, their understanding and score is under the passing grade. The objective of the research is to develop an electronic media to improve students who programmed Introduction to Linguistics course ability to master phoneme labeling. The electronic media platform is Microsoft Excel 2013. In developing the media, there are stages to build it, those are defining process, planning, building, testing, and disseminating. The research subject focuses on students of STKIP Al Hikmah year 2016/2017 who programmed Introduction to Linguistics course. The data collected are analyzed quantitatively. The result is an electronic learning media based on Microsoft Excel 2013 called OLAF that specifically developed to enhance students understanding in labeling English phonemes. Students understanding after using OLAF is significantly increasing. It is reflected through their errors in the post-test is significantly decreasing. Students’ feedback after using OLAF is satisfied because OLAF drilled and motivate them to learn phoneme labeling easier because the can use OLAF in their mobile phone.